Optimal Fiscal Regime in a Spatial Duopoly - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1994)
Extending the analysis carried out in Lambertini (1993), we investigate a horizontally differentiated duopoly in which a public authority can either tax or subsidize firms, in order to induce duopolists to choose the socially optimal locations.
Keywords: 330